Comparison of the effect of eCG and hCG treatment on the fertility in Saanen goats during the breeding season - Dogan, I; Toker, MB; Aktar, A; Yilmaz, MM; Cimen, T; Udum, D (Journal of the Hellenic Veterinary Medical Society, 2024)
This study aimed to compare the effect of hCG or eCG administered at the end of a short-term estrus synchronization treatment on the estrus parameters and pregnancy rates in non-lactating Saanen goats during the breeding season. The estrus cycles of does were synchronized with an intravaginal sponge containing 60 mg of medroxyprogesterone acetate (MAP) for five days and an injection of 125 µg of d-cloprostenol at the time of sponge insertion. Does were injected intramuscularly either 1 ml physiological saline (Control-Group; n=16) solution, 400 IU hCG (hCG-Group; n=14) or 400 IU eCG (eCG-Group; n=14) at the time of sponge removal. The estrus behavior was observed using teaser bucks and the ovulation time was monitored using transrectal ultrasonography twice daily for 96 h after the sponge removal. Does in estrus were allowed a single mating using fertile bucks. Blood samples were collected on the same days to determine serum progesterone (P4) and estradiol (E2) concentrations. No significant differences were observed between the groups in term of estrus parameters, ovarian structure and serum P4 concentrations. Although serum E2 concentration was similar between groups in the first three days. Serum E2 concentrations differed between the eCG and the other two groups on the fourth day and between the eCG and control groups on the fifth day. As a result, it can be concluded that the effects of hCG or eCG administration on estrus behavior, ovarian findings and pregnancy rate at the time of sponge removal in goats during the breeding season are similar, therefore hCG can be an alternative to eCG.